2019
DOI: 10.18203/2349-3933.ijam20194239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluate the relation between microalbuminuria and with other biochemical parameters related to complications of type 2 Diabetes

Abstract: Background: Type 2 Diabetes (T2D) with microalbuminuria have increased risk of progression to overt proteinuria, and after some time, renal failure. It is the leading cause of end-stage renal disease as a sequalae of Diabetic Nephropathy (DN) and an independent risk factor for Cardio-Vascular Diseases (CVD). Initial finding for microalbuminuria can prevent long-term complications. The objective of the present investigation was to study the relation between microalbuminuria and with other biochemical parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
2
0
0
Order By: Relevance
“…This is in line with the study conducted in Tirana, Albania which reported a signi cant association between SBP and microalbuminuria [23]. This is also supported by the study conducted in India and Taiwan which both found a signi cant association between SBP and microalbuminuria [41,43].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with the study conducted in Tirana, Albania which reported a signi cant association between SBP and microalbuminuria [23]. This is also supported by the study conducted in India and Taiwan which both found a signi cant association between SBP and microalbuminuria [41,43].…”
Section: Discussionsupporting
confidence: 90%
“…Another factor that was found to be signi cantly associated with microalbuminuria was Low density lipoprotein (LDL), in these study patients with higher LDL were almost 6times more likely to have microalbuminuria. The same is true for the study conducted by Vaidya and colleagues which found signi cant correlation between LDL and microalbuminuria [43]. This is also supported by the studies conducted in Kerala, Nigeria and Cameroon which all stated the signi cant association between LDL and micro-albuminuria [40, 44,45].…”
Section: Discussionsupporting
confidence: 70%